Removal of Ni(II) from Water by Oil Removed Coconut Residues - Srinivasan, K.; Saravanan, S. (Asian Journal of Chemistry, 2016)
Activated carbon prepared from coconut residues, an agricultural waste byproduct obtained after oil extraction, has been used for the adsorption of Ni(II) from aqueous solution. The process of uptake obeys both Freundlich and Langmuir adsorption isotherms. Kinetic studies indicate that it obeys Lagergran kinetic model. Quantitative removal of Ni(II) from 100 mL aqueous solution containing 10 mg/L of Ni(II) was observed over a pH range of 4.0 to 10.0. The suitability of this material for treating nickel-plating industry wastewater was also examined. A comparative study with a commercial granular activated carbon showed that coconut residues is 6 times more efficient compared to commercial activated carbon based on Langmuir adsorption capacity (QO).